2016
DOI: 10.1002/pmic.201600218
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cellular glycosylation of leukemia cells upon treatment with acridone derivatives yield insight into drug action

Abstract: A new acridone derivative 2-aminoacetamido-10-(3, 5-dimethoxy)-benzyl-9(10H)-acridone hydrochloride (8a) has been shown to have potent antitumor activity. In order to understand the underlying action mechanism of 8a, three compounds of the same class with structures optimized step-by-step, 9(10H)-acridone (A), 10-(3,5-dimethoxy) benzyl-9(10H)-acridone (I) and 8a, were exposed to CCRF-CEM leukemia cell to determine the N-glycosylation changes using the microfluidic HPLC-chip-TOF MS platform. N-Glycans from whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…810 Conventional MS-based methodologies, such as the analysis of cell lysate using LC (liquid chromatography)-MS, have been broadly adopted in studies of populations of cells and, consequently, resulted in averaged chemical information from cell populations analyzed. 1114 In fact, cells are unique individuals that present heterogeneity due to intrinsic (e.g., genetic information) and extrinsic (e.g., surrounding microenvironment) factors. 15 To overcome drawbacks of the conventional methods and obtain a biological signature of individual cells, a number of MS-based techniques have been developed to conduct single cell MS (SCMS) analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…810 Conventional MS-based methodologies, such as the analysis of cell lysate using LC (liquid chromatography)-MS, have been broadly adopted in studies of populations of cells and, consequently, resulted in averaged chemical information from cell populations analyzed. 1114 In fact, cells are unique individuals that present heterogeneity due to intrinsic (e.g., genetic information) and extrinsic (e.g., surrounding microenvironment) factors. 15 To overcome drawbacks of the conventional methods and obtain a biological signature of individual cells, a number of MS-based techniques have been developed to conduct single cell MS (SCMS) analysis.…”
mentioning
confidence: 99%
“…Cell, as a basic component of living organisms, contains rich biological information such as expression of genes, interaction with other cells, and metabolic response to altered microenvironment . Numerous techniques have been dedicatedly developed to study cellular constituents and reveal the biological principles of cellular metabolism. Mass spectrometry (MS), a rapidly developing technique to analyze ion species with high accuracy and sensitivity, stands out as a powerful tool to achieve efficient and reliable analysis of cell extractions. Conventional MS-based methodologies, such as the analysis of cell lysate using LC (liquid chromatography)-MS, have been broadly adopted in studies of populations of cells and, consequently, resulted in averaged chemical information from cell populations analyzed. In fact, cells are unique individuals that present heterogeneity due to intrinsic (e.g., genetic information) and extrinsic (e.g., surrounding microenvironment) factors . To overcome drawbacks of the conventional methods and obtain a biological signature of individual cells, a number of MS-based techniques have been developed to conduct single cell MS (SCMS) analysis.…”
mentioning
confidence: 99%
“…Due to the commercial availability and ease of use, microchip LC-MS has been widely applied, in proteomics [103][104][105] , but also for other applications [106][107][108] . However, because the technique is often used as an aid in solving a research problem, the use of chip LC is not necessarily revealed in literature searches.…”
Section: Applications Of Chip-format Columnsmentioning
confidence: 99%
“…Therapeutic potency of the derivative VII depended on regulating hypoglycosylation, thereby validating its use as a potential biomarker for monitoring toxicity and antitumor activity. 91 A special series of nitric oxide donating acridone-carboxamide hybrids VIII-a to VIII-f, Chart 14, were designed to be appraised for in vitro cytotoxicity against different sensitive and resistant cancer cell lines. Interestingly, the cell lines administered with hybrids VIII-c, VIII-f, and VIII-d showed an exogenous release of nitric oxide thereby improving the accretion of doxorubicin in resistant cancer cell lines upon co-administering with doxorubicin, thus validating the efflux pump targeted approach 92 of hybrid VIII.…”
Section: 23mentioning
confidence: 99%